A Optimasi Fasilitas Produksi Unit Untuk Meningkatkan Produksi Pelumas (Studi Kasus PT. Pertamina Lubricants, Dengan Fokus Production Unit Cilacap) - Kartiman Kartiman (Jurnal Teknologi Berkelanjutan, 2022)
The PLPUC company uses LOBP technology to produce lubricants. In such technology relies on machines. One of the machines is filling lithos, and the machine has several problems, namely production failure due to engine damage which results in downtime so that the lubricant production target decreases. From this problem, it is necessary to mitigate and increase production capacity to optimize facilities at PUC, then one of the mitigations is by making (PR) Preventive Replacements to schedule the replacement of engine components that will be damaged so as to reduce downtime by calculating replacement time using lean six sigma and adding base oil strorage tanks as a form of pressure maintenance for additional production capacity. Then mitigation and addition of production capacity became the purpose of this study. And part of the (LSS) Lean Six Sigma method is six sigma which serves to analyze the chances of defective lubricant products being produced, and as a waste elimination in downtime from the value stream using lean manufacturing which results in value added. Then to review the company's productivity and production quality level can be seen from the OEE (Overall Equipment Effectiveness) as an indicator of productivity and production quality level. Furthermore, from January 2010 to December 2010 PUC received an OEE value of 41.95%, and this must be increased to optimize PUC production facilities. From OEE PUC there are damaged engine components that require repair / replacement and make preventive replacement based on the service life of engine components and the level of reliability of engine performance which is expected to improve this. Preventive replacement can reduce waste in production downtime and (PM) Pressure Maintenance can increase production capacity according to the results of this research analysis. And after doing this, the initial OEE value can increase by 1.77% to 43.72%.